2017
DOI: 10.1007/s12928-016-0452-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of bleeding and repeated bleeding events in prasugrel-treated patients: a review of data from the Japanese PRASFIT studies

Abstract: Prasugrel is a third-generation thienopyridine that achieves potent platelet inhibition with less pharmacological variability than other thienopyridines. However, clinical experience suggests that prasugrel may be associated with a higher risk of de novo and recurrent bleeding events compared with clopidogrel in Japanese patients undergoing percutaneous coronary intervention (PCI). In this review, we evaluate the risk of bleeding in Japanese patients treated with prasugrel at the doses (loading/maintenance dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Risk of bleeding events is a recent topic, often mentioned with respect to antiplatelet agents in the field of PCI. The PRASFIT-ACS and PRASFIT-Elective studies conducted in Japan reported that risk of bleeding events was female sex, age ≥ 75 years, and weight ≤ 50 kg [28]. The present study also found that patients with PRU ≥ 208 after longterm DAPT (aspirin + clopidogrel) included more females, more with advanced age and lower body weight, compared to those with PRU < 208.…”
Section: Switching Between P2y 12 Inhibitors and Bleeding Eventssupporting
confidence: 71%
“…Risk of bleeding events is a recent topic, often mentioned with respect to antiplatelet agents in the field of PCI. The PRASFIT-ACS and PRASFIT-Elective studies conducted in Japan reported that risk of bleeding events was female sex, age ≥ 75 years, and weight ≤ 50 kg [28]. The present study also found that patients with PRU ≥ 208 after longterm DAPT (aspirin + clopidogrel) included more females, more with advanced age and lower body weight, compared to those with PRU < 208.…”
Section: Switching Between P2y 12 Inhibitors and Bleeding Eventssupporting
confidence: 71%
“…The incidence of MACE was numerically lower with prasugrel compared to clopidogrel, although the difference was not statistically significant (9.4% vs. 11.8%; hazard ratio 0.77; 95% CI 0.56–1.07). The incidence of the composite of major, minor, and clinically-relevant bleeding was 9.6% in both prasugrel and clopidogrel groups [29]. In the whole cohort (n = 1,363), pharmacodynamics of prasugrel (i.e., extent of platelet inhibition) was not found to be a bleeding risk factor.…”
Section: Platelet Inhibitors and Cardiac Surgerymentioning
confidence: 99%
“…In the whole cohort (n = 1,363), pharmacodynamics of prasugrel (i.e., extent of platelet inhibition) was not found to be a bleeding risk factor. The key bleeding risk factors were female gender, low body weight (≤ 50 kg), advanced age (≥ 75-year-old), and diabetes mellitus in this Japanese cohort [29]. …”
Section: Platelet Inhibitors and Cardiac Surgerymentioning
confidence: 99%
See 2 more Smart Citations